2019
DOI: 10.1039/c9cc02902h
|View full text |Cite
|
Sign up to set email alerts
|

A counter ion triggers stabilization of two geometrical isomers of a Ni(ii) dication diradical porphyrin dimer: the role of anion–π interactions

Abstract: Two isomers of a nickel(ii)porphyrinato dication diradical, isolated selectively in pure form, are stabilized exclusively by anion–π interactions, have unique and distinct electronic and spectroscopic features and display an anion-induced charge/electron transfer phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…There are only scant findings of closely related interactions within crystals that might serve as a basis of comparison. Among those pairing SbCl 3 with a N-base, 70,71 the most closely connected to the computations described above places the N of aniline 72 within 2.53 Å of Sb, fairly close to the 2.69 Å distance calculated here for the NH 3 base. Further, the θ(ClSb••N) angle in the X-ray structure is nearly precisely equal to the 165°o btained from the geometry optimization.…”
Section: 1supporting
confidence: 82%
“…There are only scant findings of closely related interactions within crystals that might serve as a basis of comparison. Among those pairing SbCl 3 with a N-base, 70,71 the most closely connected to the computations described above places the N of aniline 72 within 2.53 Å of Sb, fairly close to the 2.69 Å distance calculated here for the NH 3 base. Further, the θ(ClSb••N) angle in the X-ray structure is nearly precisely equal to the 165°o btained from the geometry optimization.…”
Section: 1supporting
confidence: 82%
“…[9] Anion-π interactions are shown to be of great importance in systems containing coordination and organometallic compounds. [32,33] Transition metal coordination is known to enhance the strength of various interactions, most notably hydrogen bonding [34] and stacking interactions. [35,36] Theoretical and experimental studies have also shown that pyridine can form anion-π interactions only if its nitrogen is coordinated with silver(I), [37] while silver(I) coordination of all nitrogen atoms of pyrazine and s-tetrazine dramatically strengthens their anionπ interactions.…”
Section: Introductionmentioning
confidence: 99%